PERENCANAAN PELABUHAN PENUMPANG LAUT TANJUNG EMAS SEMARANG - andy wahyu hermanto (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2013)
Development of port need very big expense. Therefore needed a ripe consideration and calculation to decide development of port. Decision of development of port is usually relied on considerations of economics, political, and technical. Third the consideration base each other is interconnected, but usually most determining is consideration of economics. Making of port economically have to be competent, which mean obtained by production of port should be able to close the expense of operating expenses and also invesment and conservancy for the duration of is certain, and also to get advantage.To make planning of development of port have some important the following factor : Wind, Ebb, water face elevasi, waving, election of sea characteristic, deepness of path, wide of path, layout groove sea transport, port pool, knapping of wave, dock.Planning port of passenger, factors which must be paid attention is the amount of ship dimension and passenger which step into the the port and also the availibility of farm which enough, so that development  port of passenger earn maximally. At planning of making of dock, factor which is very have an effect on  Dimension from a ship which step into the port. At planning making of Terminal passenger, factor having an effect on  the amount of existing passenger to every day added with amount of deliverer passenger. Keyword : planning port of passenger, passenger terminal and dock.